THE DESIGN AND CONSTRUCTION OF VERTICAL AXE WIND TURBINE (GIROMIL THREE HANDS TWO BLADES IN SERIAL NETHING ON EACH HAND) AS A WATER PUMP DRIVER IN GLAGAH AREA, KULON PROGO REGENCY, DAERAH ISTIMEWA YOGYAKARTA - , WIDI PRASETYA, Dr. Ing. Ir. Agus Maryono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Some latest years people realize that the price of fosiliferous energy is going up significantly. Many kinds of efforts are done to find out new sources of energy alternative energy which is abundant in our surroundings or renewable energy are done seriously. One of the so many renewable energy is wind energy. Developing wind turbine is low in cost, easy to built and very useful for the people to minimilize their dependentcy on fosiliferous energy. Wind turbine with a vertical shaft is a wind turbine with can easily be made by commond people. The price of the materials needed for constructing it is relatively not expensive, easy maintenance because it is close to the surface of the ground and it has very high torsion. The weakness of this turbine is that the number of its rotation per minute is very low. The wind turbine must be designed so that it can exstract wind energy as much as it can by reducing the scour, selecting the kind of the blade airfoil which has the highest rotation per minute. To optimalize the torsion by emphazising the spokes of the rotor. Two blades airfoil which are serial arranged will be able to optimalize exstracting the energy of the wind. The energy of the wind manipulated by the wind turbine can be used to move the water pump or it can also be used as an electric generator.